Personality Traits and Financial Management Behavior of University Students - Obenza, Brandon; Torrefranca, Johanna Paula; Amarilla, Jerald Dave; Pandamon, Jobea; Encarnacion, Shaira; Getalado, Genesis; Azis, Abdulnaim H. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This non-experimental quantitative study investigated the association of the five big personality traits with the financial management behavior (FMB) of university students in Davao City. Using stratified random sampling, three hundred twenty-two respondents participated in the survey. The adopted questionnaires used in collecting the data were tested using Cronbach's Alpha and Cronbach’s Alpha to ascertain their reliability and validity. Using regression analysis through SmartPLS 4.0 software, the findings revealed that conscientiousness (β=0.296, p-value=0.000), extraversion (β=0.181, p-value=0.001), and openness (β= -0.110, p-value=0.045) showed significant link towards FMB. Nevertheless, Agreeableness (β= -0.056, p-value=0.324) and Neuroticism (β= -0.034, p-value=0.553) were insignificant. Finally, the regression model explains that 14.30% of the variance in FMB of university students (F = 10.540, P-value = 0.000, R2 = 0.143, Adjusted R² = 0.129).